The Effectiveness of Direct Oral Anticoagulation in the Treatment of Left Ventricular Thrombus in Noncompaction Cardiomyopathy: A Case Report - Ossama Maadarani; Leila Bigdelu; Harikrishna Rajendran; Zouhair Bitar (Clinical Case Reports)
ABSTRACT The use of direct oral anticoagulants (DOACs) in the treatment of left ventricular thrombus (LVT) associated with specific types of cardiomyopathy like noncompaction cardiomyopathy (NCCM) is not established. We report a case of LVT in an NCCM patient treated with DOAC with complete resolution. To the best of our knowledge, this is the second case of successful treatment of LVT related to NCCM with DOACs.